Evidence-Based Standard Setting: Establishing a Validity Framework for Cut Scores. (March 2013) - McClarty, Katie Larsen; Way, Walter D.; Porter, Andrew C.; Beimers, Jennifer N.; Miles, Julie A.
Performance standards are a powerful way to communicate K–12 student achievement (e.g., proficiency) and are the cornerstone of standards-based reform. As education reform shifts the focus to college and career readiness, approaches for setting performance standards need to be revised. We argue that the focus on assessing student readiness can move performance standards toward an increasingly empirical grounding, leading to more meaningful and understandable standards for student achievement and better guideposts for instructional improvement. Specifically, we describe and illustrate the processes and practices associated with evidence-based standard setting, taking as our example a specific application in the American Diploma Project Algebra II End-of-Course Exam, which was developed as an indicator of college readiness.